Internet Science Third International Conference, INSCI 2016, Florence, Italy, September 12-14, 2016, Proceedings - Bagnoli, Franco; Satsiou, Anna; Stavrakakis, Ioannis; Nesi, Paolo; Pacini, Giovanna; Welp, Yanina; Tiropanis, Thanassis; DiFranzo, Dominic (Information Systems and Applications, incl. Internet/Web, and HCI, 2016)
This book constitutes the proceedings of the Third International Conference on Internet Science held in Florence, Italy, in September 2016. The 25 papers presented were carefully reviewed and selected for inclusion in this volume. They were organized in topical sections named: collective awareness and crowdsourcing platforms¸ collaboration, privacy and conformity in virtual/social environments; internet interoperability, freedom and data analysis; smart cities and sociotechnical systems.